Impact of binge eating disorder in the psychopathological profile of obese women - Fandiño, Julia; Moreira, Rodrigo O.; Preissler, Carolina; Gaya, Caroline W.; Papelbaum, Marcelo; Coutinho, Walmir F.; Appolinario, Jose C. (Comprehensive psychiatry, 2010)
Our objective was to evaluate the psychopathological profile of obese women with binge eating disorder (BED) using the Symptom Checklist-90 (SCL-90). Two hundred twelve obese women who seek for weight loss treatment were sequentially selected to participate in the study. Binge eating disorder was diagnosed using the Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition. Binge eating disorder severity was assessed using Binge Eating Scale. Depressive symptoms were assessed using Beck Depression Inventory. The psychopathological profile was assessed using the SCL-90. Binge eating disorder was diagnosed in 54 patients (26.6%). Obese patients with BED presented significant higher scores in all domains of SCL-90 ( P < .05 for all) in comparison with obese patients without BED. A significant relationship was found among Binge Eating Scale, Beck Depression Inventory, and all domains of the SCL-90 ( P < .05 for all). After linear regression, obsessivity-compulsivity ( P = .03), interpersonal sensitivity ( P = .0064), paranoid ideas ( P = .03), and psychoticism ( P = .01) were independently related to the severity of BED. Obese women with BED presented a more severe psychopathological profile than obese controls. Among all, obsessivity-compulsivity, interpersonal sensitivity, paranoid ideas, and psychoticism seem to be strongly linked to BED severity.